Literasi Keuangan, Gaya Hidup, Dan Pendapatan: Faktor Penentu Dalam Manajemen Keuangan Pribadi - afasya, nabila; ardila, isna (JURNAL MANAJEMEN DAN BISNIS, 2025)
This study aims to identify and analyze the influence of financial literacy, lifestyle, and income on personal financial management. This research uses an associative approach to identify the relationships between the variables studied. This study adopts an associative approach to identify the relationships among the variables being examined. The approach used is quantitative, where the data is analyzed through numerical processing, and conclusions are drawn based on statistical testing using the Partial Least Square (PLS) method, processed with SmartPLS4 software. The research subjects are students enrolled in the Accounting Department of the Faculty of Economics and Business at Universitas Muhammadiyah Sumatera Utara (UMSU), with a total population of 966 students. The sample consisted of 91 respondents, determined using the Slovin formula as the sampling technique. The results of data analysis indicate that financial literacy has a significant influence on personal financial management. In addition, lifestyle also has a significant impact on personal financial management, as does income, which was also found to significantly affect the personal financial management of Accounting students at FEB UMSU.